Enhancing Pedagogical Competence in Developing Lesson Plans through Academic Supervision for Teachers at SMP KR. Tagari - Rosalina Mada (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2021)
The aim of this school action research is to improve the teachers' competence in developing lesson plans (RPP) through academic supervision at SMP Kr. Tagari in Tallunglipu District, North Toraja Regency. The objective is to enable teachers to create lesson plans that align with the respective subject competencies and serve as a reference for the teaching process, thereby ensuring that students can achieve the minimum proficiency criteria. The research method employed in this study is Action Research, which consists of two cycles. Each cycle includes Planning, Implementation, Observation, and Reflection. The research findings indicate the following (1) In the component of formulating learning objective indicators, there was an improvement from an initial competence level of 61.1% to 67.8% in Cycle I and further increased to 72.2% in Cycle II; (2) In the component of determining teaching materials and resources, the competence level increased from 43.3% to 71.1% after Cycle I and further strengthened to 72.2% in Cycle II, (3) In the component of selecting teaching strategies and methods, which includes learning steps and determining time allocation, a significant improvement was observed. The competence level increased from 53.3% initially to 62.2% in Cycle I and further rose to 71.1% after Cycle II; (4) Although there was not a substantial improvement, the component of selecting media and teaching aids also showed an increase from 53.3% at the beginning of the research to 61.1% after Cycle I, and ultimately reached 71.1% after Cycle II; (5) A significant improvement can be observed in the component of planning learning evaluation. It started at 45.6% and increased to 60.0% at the end of Cycle I, ultimately achieving 75.6% by the end of Cycle II. Based on the research data, it can be concluded that academic supervision can enhance teachers' competence in developing lesson plans (RPP) at SMP Kr. Tagari in Tallunglipu District, North Toraja Regency.